2019
DOI: 10.1111/jhn.12617
|View full text |Cite
|
Sign up to set email alerts
|

The tension between efficiency and effectiveness: a study of dietetic practice in primary care

Abstract: Background: Primary healthcare dietitians have a vital role to play in the prevention and management of chronic disease. Working in primary care requires efficient and effective management of practice to ensure client and practitioner needs are met. The present study aimed to explore the way in which primary care dietitians in Australia view the constructs of efficiency and effectiveness within the context of their practice. Methods: The study used an exploratory qualitative design within a pragmatist framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…Effectiveness, efficiency and person-centredness were the WHO quality elements most frequently addressed in this review. Effectiveness and efficiency were commonly addressed together, which complements the findings in a qualitative study by O'Connor et al 38 in which primary care dietitians perceived the two elements as being intertwined. Only two RCTs in the current review employed at least one form of technology, which is surprising given that previous research has identified that dietitians perceive technology as improving both efficiency and effectiveness.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 56%
See 1 more Smart Citation
“…Effectiveness, efficiency and person-centredness were the WHO quality elements most frequently addressed in this review. Effectiveness and efficiency were commonly addressed together, which complements the findings in a qualitative study by O'Connor et al 38 in which primary care dietitians perceived the two elements as being intertwined. Only two RCTs in the current review employed at least one form of technology, which is surprising given that previous research has identified that dietitians perceive technology as improving both efficiency and effectiveness.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 56%
“…Only two RCTs in the current review employed at least one form of technology, which is surprising given that previous research has identified that dietitians perceive technology as improving both efficiency and effectiveness. [38][39][40] This may be a result of barriers to technology use, which include not being familiar with available technology or how to use it, and appropriateness for the patient population. 40 Studies that addressed person-centredness focused on developing the patient's self-management skills rather than the dietitian's counselling skills.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%
“…This tension has been identified by Allied Health Professionals Australia who contend that the “current fees [for the Medicare rebate] remain well below the true cost of providing adequate patient care and are limiting access for many of those with the greatest need.” [ 41 ]. In addition, a qualitative study exploring Australian private practicing dietitians understanding of efficiency and effectiveness reported that finding a balance between efficiency and effectiveness was difficult when working in small business or as a contractor [ 44 ]. This paper posited that increased use of health technology may help streamline administration duties that curtailed private practitioners’ billable hours [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a qualitative study exploring Australian private practicing dietitians understanding of efficiency and effectiveness reported that finding a balance between efficiency and effectiveness was difficult when working in small business or as a contractor [ 44 ]. This paper posited that increased use of health technology may help streamline administration duties that curtailed private practitioners’ billable hours [ 44 ]. Lack of time, secondary to inadequate remuneration for time in dietetic practice, has previously been shown to hinder patient-centred care [ 42 ], the use of VLEDs [ 27 ], dietary assessment [ 45 ], and best practice in obesity management [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…O nutricionista da atenção primária possui um papel vital à promoção e proteção da saúde 25 . Uma das ações dentro das unidades de saúde são os atendimentos a pessoas com doenças crônicas não transmissíveis e, neste estudo, foi considerada uma atividade relevante para os usuários.…”
Section: Introductionunclassified